Evaluation of Epithelial Cells of Oral Mucosae in Patients with Fixed Orthodontic Appliance - A Shiva; F Moaddabi; S Arab; M Khatami; M Zamanzadeh; M Koochek Dezfouli; A Hossein Nataj; P Namdar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Orthodontic appliances are usually in contact with the oral mucosa for a long time due to the length of the long-term treatment and are associated with problems due to the continuous contact and friction created. This study was conducted to investigate the epithelial cells of the mucosa of patients with fixed orthodontic appliances. Methods: In this cross-sectional study, smears were collected from three separate areas in 150 patients referred to the dental clinic of Mazandaran University: Area A (slide A): oral mucosa exposed to friction caused by orthodontic brackets, area B (slide B): oral mucosa exposed to friction with the tube on the orthodontic tape and Area C (slide C): oral mucosa without friction, i.e., the lower area of the oral cavity (control area). For histomorphometric analysis, each slide was evaluated with Papanicolaou staining using a light microscope, and the nuclear area (NA), cytoplasmic area (CA), and the ratio of nuclear area to cytoplasmic area (NA/CA) were recorded in square micrometers. Findings: The mean NA was 65.66±22.11, CA was 717.37±1846.53, and NA/CA was 0.037±0.010 square meters. The difference in NA and CA between slides was significant )p<0.001) (slide A Conclusion: The findings of the study indicate that fixed orthodontic treatment has a significant impact on the nuclear and cytoplasmic area of affected areas compared to non-affected areas. Only some degree of inflammation may be seen in the areas exposed to the orthodontic appliance.